2021
DOI: 10.12998/wjcc.v9.i22.6268
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of effect of whole-body vibration training on balance and walking function in stroke patients

Abstract: BACKGROUND Dysfunction in stroke patients has been a problem that we committed to solve and explore. Physical therapy has some effect to regain strength, balance, and coordination. However, it is not a complete cure, so we are trying to find more effective treatments. AIM To observe the effect of whole-body vibration training (WVT) on the recovery of balance and walking function in stroke patients, which could provide us some useful evidence for planning rehabilitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…After reading the titles and abstracts, 122 studies were selected. Then, after reading the full texts, 98 studies were discarded because they did not meet the inclusion and exclusion criteria, and 22 studies were finally included ( van Nes et al, 2006 ; Brogårdh et al, 2012 ; Chan et al, 2012 ; Guo et al, 2015 ; Choi et al, 2016 , 2017 ; Gu and Hwangbo, 2016 ; Qianhao et al, 2018 ; Lee, 2019 ; Zhanyu et al, 2019 ; Zhen-hua et al, 2019 ; Sade et al, 2020 ; Xin-xin et al, 2020 ; Ijaz Ahmed Burq et al, 2021 ; Jin-Ming et al, 2021 ; Kim and Lee, 2021 ; Xie et al, 2021 ; Yan et al, 2021 ; Chuan et al, 2022 ; Le et al, 2022 ; Wei and Cai, 2022 ; Zhenying et al, 2022 ). The process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reading the titles and abstracts, 122 studies were selected. Then, after reading the full texts, 98 studies were discarded because they did not meet the inclusion and exclusion criteria, and 22 studies were finally included ( van Nes et al, 2006 ; Brogårdh et al, 2012 ; Chan et al, 2012 ; Guo et al, 2015 ; Choi et al, 2016 , 2017 ; Gu and Hwangbo, 2016 ; Qianhao et al, 2018 ; Lee, 2019 ; Zhanyu et al, 2019 ; Zhen-hua et al, 2019 ; Sade et al, 2020 ; Xin-xin et al, 2020 ; Ijaz Ahmed Burq et al, 2021 ; Jin-Ming et al, 2021 ; Kim and Lee, 2021 ; Xie et al, 2021 ; Yan et al, 2021 ; Chuan et al, 2022 ; Le et al, 2022 ; Wei and Cai, 2022 ; Zhenying et al, 2022 ). The process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 studies ( van Nes et al, 2006 ; Brogårdh et al, 2012 ; Gu and Hwangbo, 2016 ; Qianhao et al, 2018 ; Sade et al, 2020 ; Xin-xin et al, 2020 ; Jin-Ming et al, 2021 ; Kim and Lee, 2021 ; Xie et al, 2021 ; Yan et al, 2021 ; Le et al, 2022 ; Wei and Cai, 2022 ; Zhenying et al, 2022 )reported the effect of WBV training on BBS in stroke patients, with substantial heterogeneity among them ( p < 0.001, I 2 = 80%). A random effects model was used to analyze the data (MD = 4.08, 95%CI [2.39, 5.76], p < 0.001; Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations